Isoniazid Induced Generalized Lichenoid Drug Eruption: An Unusual Offender - Singh, Pratima; Nathiya, Deepak; Jain, Sonal; Raj, Preeti; Suman, Supriya; Tomar, Balvir Singh (Indian Journal of Pharmacy Practice)
Introduction: Isoniazid also known as isonicotinic acid hydrazide is first line drug in anti-tubercular regimen. We report the case of lichenoid drug eruption due to this drug. Case-Report: A Sixty four-year old man received treatment for transverse myelitis with pulmonary TB. After almost four months of initiation of regimen he developed viloaceous lesions first from back and gradually involving B/L extremities. A skin punch biopsy is indicative of drug-induced lichenoid drug eruption. Isoniazid dechallenge and rechallenge confirmed the diagnosis of “Isoniazid induced lichenoid Drug eruption”. Discussion: Incidence of isoniazid induced CADR is 0.98%. Diagnosis decisionmaking should be on the basis of critical analysis of case. Role of Pharmacovigilance is crucial to understand quality and frequency of adverse drug reactions.
Keywords: Lichenoid drug eruption; Isoniazid; Tuberculosis; Cutaneous adverse drug eruption; ATT.